A Simultaneous Decision Model for Production, Marketing and Finance - Damon, William W.; Schramm, Richard (Management Science, 1972)
The Holt, Modigliani, Muth, and Simon production scheduling model is extended to incorporate variables reflecting marketing and working capital management in a cash flow formulation. A constrained nonlinear program is dervied for which a local optimal solution is discovered employing the SUMT program. Reasonable values are are assigned to the parameters and the relative profitability of such a simultaneous formulation, compared to a sequential model, is tested. Initial results demonstrate an improvement of 25% by solving for the optimal values of the functional decision variables simultaneously.